A societal perspective on self-employment – Sweden as an example. Issue 7 (3rd July 2021) - Berggren, Caroline; Olofsson, Anders
ABSTRACT: European Union policies emphasise the importance of entrepreneurship and self-employment to maintain economic growth, a solution influenced by the USA and research from schools of business. There are expectations of higher education graduates that they are innovative, will start businesses and will employ others. However, transferring a solution from one country to another may not be as simple as that. This study questions the recommendations made in EU policies which mainly focus on how to support individuals to become self-employed. Extensive data from the Swedish population registry of approximately 90, 000 tertiary-educated people, all born in the mid-1970s, is used to analyse the extent to which this group became self-employed. Results show that societal and cultural differences need to be considered when creating such policies.